Governing business process offshoring: Properties, processes, and preferred modes - Luo, Yadong; Wang, S.; Jayaraman, V.; Zheng, Q. (Pergamon, 2013)
This article examines an important yet understudied issue-the governance mode for business process offshoring (BPO). By applying transaction cost economics and organizational control perspective in the global BPO context, we suggest that BPO's governance mode (foreign captive, joint venture, and independent vendor) is determined by task features, such as knowledge specialization, information security, and process codifiability, and by needed process integration, horizontally between departments and units within the provider and vertically between the provider and its global client and its local subcontractor. Findings from our analysis of 308 global BPO units in India and China confirm our hypotheses.